Observations on the terrestrial leech Haemopis septagon Sawyer & Shelley, 1976 (Annelida: Hirudinea) from the Outer Banks, North Carolina, USA, with a revision of the species - Sawyer, Roy T. (Zootaxa, 2019)
The terrestrial leech Haemopis septagon Sawyer & Shelley, 1976, is indigenous to the Great Dismal Swamp and environs of northeastern North Carolina and southeastern Virginia, USA. Ever since its discovery in 1895 at Lake Drummond in the Dismal Swamp, this elusive species has been recognized as taxonomically aberrant. For example, it is the only jawed leech in the United States with seven annuli between gonopores, and the only one with sixteen complete (5-annulate) segments, both highly conserved characters in the Hirudinidae.                The discovery of two populations of H. septagon in the Albemarle Peninsula in the Outer Banks region of North Carolina afforded an opportunity to investigate the taxonomy and biology of this inadequately characterized species. Its description in this study is the first comprehensive account of the external and internal anatomy of this species since its incomplete original description in 1976. This study is also an opportunity to correct errors in the incomplete original description, and to elucidate morphological and developmental variability of taxonomic significance. Evidence is presented for the first time of a possible aquatic or semi-aquatic form of H. septagon.                These Albemarle individuals were compared to the holotype from Durham County, NC, specimens from southeastern Virginia and a terrestrial leech recently reported from southern New Jersey. All of these fall within the variability demonstrated in this study for the Albemarle populations, and are accordingly recognized as the same species, H. septagon.  Consequentially, Haemopis ottorum Wirchansky & Shain, 2010, is recognized as a junior synonym of Haemopis septagon.